Effectiveness of Leaflet-Based Health Education on Pregnant Women’s Knowledge of Anemia Prevention: A Quasi-Experimental Study at Paniaran Community Health Center, North Tapanuli, Indonesia - Riance Mardiana Ujung; Janner Pelanjani Simamora (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Anemia in pregnancy remains a major public health problem in Indonesia and is associated with serious maternal and neonatal complications, including hemorrhage, low birth weight, prematurity, and stunting. Adequate maternal knowledge is essential for prevention, and simple educational media such as leaflets may help improve awareness.  This study aims to analyze the effect of leaflet-based health education on pregnant women’s knowledge of anemia prevention. A quasi-experimental one-group pretest–posttest design was conducted from July to December 2025 at Paniaran Community Health Center, North Tapanuli Regency. Twenty-five pregnant women attending antenatal classes were recruited. Knowledge was assessed using a structured questionnaire before and 14 days after the intervention. Data were analyzed using the Wilcoxon signed-rank test with a significance level of 0.05.  Prior to the intervention, 72% (n=18) of respondents demonstrated good knowledge; this proportion increased to 92% (n=23) after the intervention. The Wilcoxon test indicated a statistically significant improvementin knowledge (p = 0.011 < 0.05).  Leaflet-based health education significantly improved pregnant women’s knowledge of anemia prevention. This approach can serve as a simple, low-cost educational tool to strengthen anemia prevention within antenatal care services.Keywords: Anemia In Pregnancy, Maternal Health Education, Health Promotion, Iron Deficiency Anemia Prevention, Leaflet.